(untitled) (CIPEEX, 2022)
CHOLANGIOCARCINOMA (CCA) IS A CANCER THAT ARISES FROM THE DEGENERATION OF THE EPITHELIUM OF THE BILE DUCTS, FROM THE SMALL INTRAHEPATIC BILE DUCTS TO THE COMMON BILE DUCT. THIS PAPER REPORTS THE CASE OF A FEMALE PATIENT OF 78 YEARS, DIAGNOSED WITH A CHOLANGIOCARCINOMA. THE CCA IS A CANCER OF THE BILE DUCT EPITHELIUM, WHICH WHEN LOCATED IN THE BIFURCATION OF THE HEPATIC DUCTS IS CALLED KLATSKIN TUMOR (TK) OR PERI-HILAR, WHICH HAS A LOW GLOBAL INCIDENCE AND HIGH LETHALITY. THE PATIENT PRESENTED WEIGHT LOSS, 12 KG AT 2 MONTHS, CONSTIPATION AND TWO EPISODES OF EMESIS. PHYSICAL EXAMINATION: GOOD GENERAL CONDITION, JAUNDICE 2 +/- 4 +, HYPOCORATED 1 +/- 4, GLOBUS ABDOMEN AND PAINFUL DIFFUSELY, WITH PALPABLE MASS IN RIGHT HYPOCHONDRIUM AND JAUNDICE IN PERIUMBILICAL REGION. TEST RESULTS: TOTAL BILIRUBIN, DIRECT AND INDIRECT INCREASED, AS WELL AS TRANSAMINASES AND TUMOR MARKER CA 19-9; IMAGING STUDIES WITH INTRAHEPATIC BILIARY DILATATION AND EXPANDING INFILTRATIVE FORMATION IN THE HEPATIC WIRE WITH EXTENSION TO THE PARENCHYMA. SURGICAL TREATMENT WAS CONTRAINDICATED BECAUSE OF THE COMORBIDITIES PRESENTED BY THE PATIENT, THEREFORE, SHE WAS OFFERED PALLIATIVE THERAPY. DESPITE THE COMMITMENT OF THE HEALTH TEAM IN CHOOSING THE MOST APPROPRIATE THERAPY FOR THE PATIENT, THE CASE EVOLVED ACCORDING TO WHAT WAS PREDICTED IN THE EXISTING LITERATURE, AND THE PATIENT DIED.